Reproducibility and validity of anterior implant esthetic indices: A review - Gunjan Srivastava; Swagatika Panda; Saurav Panda; Subrat Kumar Padhiary; Sitansu Sekhar Das; Massimo Del Fabbro (Wolters Kluwer Medknow Publications, 2020)
Background: The purpose of this review was to narrate about the reproducibility and validity of different indices evaluating esthetic aspects in anterior single implant-supported restorations. Materials and Methods: An electronic search of Medline, Scopus, Embase, Cochrane Central, and Web of Science databases was performed using the keywords "dental implants," "anterior esthetics," "esthetic score," and "esthetic index." Besides, a manual search of dental implant journals was carried out. Results: The electronic search revealed 932 titles. After further review, 14 articles fulfilled the eligibility criteria and were included in this review. Because of the heterogeneity of the study designs, interventions, and parameters used for assessment of esthetics, no meta-analysis could be performed. Conclusion: Many indices have been proposed for the evaluation of the esthetic aspects of single implant-supported reconstructions in the anterior maxilla. All of them have some advantages and drawbacks that this review pointed out. The evidence level of studies used for the validation of these indices is poor. It is necessary to achieve a consensus on the tools for assessment of the esthetic aspect and perform evidence-based studies to validate an appropriate index.